2001
DOI: 10.1097/00007890-200105150-00019
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Inhaled Nitric Oxide and Pentoxifylline on Ischemia/Reperfusion Injury After Lung Transplantation

Abstract: The marked decrease in the incidence of allograft dysfunction compared with two historical control groups suggests that PTX and inhaled NO given before and throughout reperfusion are protective against I/R injury in the setting of clinical transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 23 publications
1
28
0
6
Order By: Relevance
“…16 In patients with sickle cell disease, inhaled NO (80 ppm) does not modify the erythrocyte oxygen affinity, even when associated with a modest increase in methemoglobin. 32,33 Here, we found that inhaled NO (40 ppm) ameliorates red blood cell dehydration in SAD mice exposed to 46 hours of hypoxia, with an increase in red blood cell K ϩ content. We previously reported that hypoxia-induced red blood cell dehydration in SAD mice is mostly mediated by the Ca 2ϩ -activated K ϩ channel and prevented by its specific inhibitor, clotrimazole.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…16 In patients with sickle cell disease, inhaled NO (80 ppm) does not modify the erythrocyte oxygen affinity, even when associated with a modest increase in methemoglobin. 32,33 Here, we found that inhaled NO (40 ppm) ameliorates red blood cell dehydration in SAD mice exposed to 46 hours of hypoxia, with an increase in red blood cell K ϩ content. We previously reported that hypoxia-induced red blood cell dehydration in SAD mice is mostly mediated by the Ca 2ϩ -activated K ϩ channel and prevented by its specific inhibitor, clotrimazole.…”
Section: Discussionmentioning
confidence: 73%
“…Gene expression profiling of lung tissue pointed to the specific induction of genes involved in the response to ischemic stress and microcirculation remodeling. Because NO is a potent vasodilator and inhibitor of vascular remodeling and also affects the multistep cascade events involved in leukocyte, platelets, and endothelial activation, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] we have investigated whether inhaled NO, which diffuses directly from alveoli to pulmonary vascular smooth muscle, could prevent lung injury consecutive to pulmonary ischemic/reperfusion damage and studied its mechanism(s) of action.…”
Section: Introductionmentioning
confidence: 99%
“…Aprotinin's effects are especially beneficial in light of a retrospective study of 180 lung transplant patients, which demonstrated a significant decrease of severe posttransplant LIRI, largely through the attenuation of neutrophil activity (24). Thabut et al (198) found a marked decrease in the incidence of allograft dysfunction (by mortality, pulmonary edema, lung function, and duration of mechanical ventilation) after lung transplantation when administrating pentoxyfilline and inhaled NO before and during perfusion compared with historical controls.…”
Section: Therapeutic Possibilitiesmentioning
confidence: 99%
“…Studies of the anti-inflammatory effects of PTX in vivo have focused attention on tissue injury after ischemia. Thus, in vivo PTX treatment reduced ischemia-reperfusion injury in the lung (Thabut et al, 2001), intestine (Sener et al, 2001), liver (Iwamoto et al, 2002), kidney (Kim et al, 2001), spinal cord (Savas et al, 2002), and brain of different animal species including rats, mice, and dogs (Toung et al, 1994;Sirin et al, 1998;Eun et al, 2000). Inflammatory processes accompany tissue injury regardless of the organ system involved, and chronic inflammation may predispose to ischemia in peripheral organs and to brain damage (Lindsberg and Grau, 2003).…”
mentioning
confidence: 99%